Boundary-value problems for nonlinear third-order q-difference equations - Bashir Ahmad (Electronic Journal of Differential Equations, 2011)
This article shows existence results for a boundary-value problem of nonlinear third-order q-difference equations. Our results are based on Leray-Schauder degree theory and some standard fixed point theorems.